Penerapan Model PBL Pada Materi Mengembangkan Budaya Kasih Dalam Meningkatkan Kemampuan Bernalar Kritis Fase F SMK Negeri 3 Pematangsiantar - Elrismora Elrismora (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Application Of The Pbl Model In Improving Class Students' Critical Reasoning Ability XI KC 1 FASE F SMK NEGERI 3 Pematangsiantar In Developing Materials Culture Of Love. 1) Application of the PBL Model can improve the Critical Reasoning Ability of Class XI KC 1 FASE F SMK NEGERI 3 Pematangsiantar Students in the Material of Developing a Culture of Love. 2) How the implementation of the PBL Model can improve the Critical Reasoning Ability of Class XI KC 1 FASE F SMK NEGERI 3 Pematangsiantar Students in the Material of Developing a Culture of Love. This type of research is PTK (Classroom Action Research). The subjects of this research were students of class XI KC 1 FASE F SMK NEGERI 3 Pematangsiantar. The results of this research show that, 1) Learning using the PBL model shows a good response to improving students' critical reasoning abilities in understanding the material for developing a culture of love in class XI KC1 SMK N 3 Pematangsiantar, giving satisfaction to teachers or researchers. It can be seen from the data obtained, before using the PBL model the students' average score on developing a culture of love was classified as very low with a score of 64.61. After using PBL the students' average score increased in cycle I with a score of 72.69. Continuing to cycle II the students' average score was 82.69, thus the PBL model is very suitable for improving students' critical reasoning skills regarding developing a culture of love. 2) Students' critical reasoning abilities after using the PBL model material develop a culture of love for students' learning after using class XI KC1 SMK N 3 Pematangsianar media with student learning outcomes increasing and achieving completeness. Because the learning process using the PBL model provides satisfaction for both teachers and students. Teachers are enthusiastic and students become active and cheerful during the learning process.